Sirtuins—Novel Regulators of Epigenetic Alterations in Airway Inflammation - Wu, Shunyu; Liu, Huanhai (Frontiers in Genetics, 2022)
Histone modification is an important epigenetic alteration, and histone deacetylases are involved in the occurrence and development of various respiratory diseases. Sirtuins (SIRTs) have been demonstrated to play important roles in the formation and progression of chronic inflammatory diseases of the respiratory tract. SIRTs participate in the regulation of oxidative stress and inflammation and are related to cell structure and cell localization. This review summarizes the roles and mechanisms of SIRTs in airway inflammation and describes the latest research on SIRT modulators, aiming to provide a theoretical basis for the study of potential epigenetic alteration-inducing drug targets.